2017
DOI: 10.22377/ijgp.v11i02.1031
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Skin ageing is a complex multifactorial process occurring in all living beings. It generally comprises two independent and distinct processes, i.e., intrinsic, age-dependent or chronological aging and premature aging, or photoaging which is the result of undue exposure of the skin to ultraviolet (UV) radiations. Photoaging can be prevented or the effects of photoaging can be reduced by the use of certain anti-aging and anti-wrinkle agents. The extracellular matrix (ECM) which forms the outermost part of skin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Furthermore, many studies showed that skin aging and skin wrinkling may be reduced by the action of the antioxidant activity of various botanical extracts [58,59]. Aumeeruddy-Elalfi et al [22] showed that the inhibitory potential of essential oils extracted from some medicinal plants make them potential candidates for the cosmetic (skin aging) and pharmaceutical industries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many studies showed that skin aging and skin wrinkling may be reduced by the action of the antioxidant activity of various botanical extracts [58,59]. Aumeeruddy-Elalfi et al [22] showed that the inhibitory potential of essential oils extracted from some medicinal plants make them potential candidates for the cosmetic (skin aging) and pharmaceutical industries.…”
Section: Discussionmentioning
confidence: 99%
“…These components were reported to exhibit anti-aging properties [50]. Moreover, limonene, which was not present at elevated levels in the study's EO (Table 1), was reported to display higher anti-inflammatory properties [16,51]. In addition to their individual activities, these compounds could display a synergistic action [16,44].…”
Section: Collagenase and Elastase Inhibitionmentioning
confidence: 99%
“…Laserine (28) Weak cytotoxicity against HL-60 (acute promyelocytic leukemia) cancer cell line [118], inhibitor of skin photo-aging [119]. Table 1.…”
Section: Secondary Metabolite Biological Activitiesmentioning
confidence: 99%